Effect of Breast Care and Oxytocin Massage on Breast Milk Production: A study in Sukoharjo Provincial Hospital - Rahayuningsih, Tutik; Mudigdo, Ambar; Murti, Bhisma (Journal of Maternal and Child Health, 2016)
Background: The prevalence of exclusive breast feeding was 39.05% in Sukoharjo in 2015, which is far bellow the national target of 80%. A study has shown that massage oxytocin increases oxytocin (OT) hormone release, and eventually decreases adrenocorticotropin hormone (ACTH), nitric oxide (NO), and beta-endorphin (BE). This OT hormone release will increase milk ejection, which facilitate milk production. This study aimed to investigate the effect of breast care and oxytocin massages on breast milk production in postÃ¢â¬âpartum mothers.Subjects and method: This was a Randomized Controlled Trial (RCT), conducted at Sukoharjo Hospital, Central Java 19 October to November 18, 2016. A total of 90 post Ã¢â¬â partum mothers were selected at random and then allocated into breast care group and oxytocin massage group. The dependent variable was breast milk production. The independent variable was breast care and oxytocin massage. Changes in breast milk production before and after intervention between the two groups were tested by Mann-Whitney test.Results: The increase in breast milk production in breast care and oxytocin massage group (meanÃÂ =ÃÂ 17.37, SDÃÂ =ÃÂ 9.70)ÃÂ was larger than that of the control group (meanÃÂ =ÃÂ 1.58, SDÃÂ =ÃÂ 1.69), and it was statistically significant (pÃÂ <0.001).Conclusion: Breast care and oxytocin massage can significantly increase breast milk production. Post-partum mothers are recommended to practice breast care and oxytocin massage, in order to increase breast milk production.Keywords:ÃÂ breastÃÂ care, oxytocin massage, breast milk production.Correspondende:ÃÂ Tutik Rahayuningsih. School of Health Polytechnics, PoltekkesÃÂ BhaktiÃÂ Mulia,ÃÂ Surakarta. Email: tutikrahayu_abm@yahoo.co.idJournal of Maternal and Child Health (2016), 1(2): 101-109https://doi.org/10.26911/thejmch.2016.01.02.05